Pelatihan Pengenalan dan Pemanfaatan Biji Kopi untuk Memulai Bisnis Kopi - Uturestantix Uturestantix; Quincy F. Kambuaya; Idham Khaliq (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: The coffee industry is one of the rapidly growing agribusiness sectors and provides great opportunities for small and medium-sized businesses, especially in the downstream sector such as the processing of ready-to-serve coffee beans. In Jayapura City, the increasing growth of coffee shops has not been matched by the availability of professional roasting services and human resources with technical skills in coffee bean processing. Therefore, this community service activity was carried out with the aim of increasing the capacity of the community and MSME partners in recognising coffee bean types, understanding the roasting and grinding process, and producing ready-to-serve coffee products to support the needs of local coffee shops. Method: The activity was carried out through the stages of target identification, preparation, socialisation, practical training in roasting and brewing, mentoring, and evaluation using questionnaires and hearings. Results: The results of the activity showed that participants enthusiastically attended the training and experienced an increase in knowledge and skills in distinguishing between Arabica and Robusta coffee types, understanding roasting temperature and duration, grinding techniques according to brewing needs, and the basics of coffee cupping for taste observation